Analisis RFID Pasif Untuk Inventory Monitoring Dalam Mendukung Industri 4.0 - Gamaliel, Yoyok; Sirait, Tamsir Hasudungan; Nugroho, Tunggul Arief; Juhandi, Triandi Shafa (Jurnal Telematika, 2019)
Nowadays, the production process in a factory demandsa rapid adaptation process to keep up with the sustainable market change. Industry 4.0, known as 4 th industry revolution, is a production concept in which all factors of the supply chain production are integrated. The process of gathering, processing and displaying information is significant in the production process of industry 4.0. The product-related information consists of the data of material/product, product location, or product status. The production process starts from the availability of the raw materials in the storage. The list of available materials is defined as inventory. Thus, the monitoring system starts from inventory which monitor the data of material itself. The technology of RFID (Radio Frequency Identifier) sensor helps to identify the materials easily, effectively and efficiently. The RFID tags attached to the materials/products will provide the detailed information about those materials. This research focuses on analyzing the performance of RFID reader using passive tag as well as the process of scanning and parsing of data which then used for monitoring process. The used of writeable tags is recommended. The result of RFID system test show that above 70 percent can be utilized as inventory monitoring.Proses produksi di suatu pabrik sekarang ini memerlukan proses adaptasi yang cepat untuk mengikuti perubahan pasar yang berkelanjutan. Industri 4.0 yang dikenal sebagai revolusi industr keempat adalah konsep produksi di mana semua faktor dalam rantai pasok produksi sudah terintegrasi. Proses produksi yang mendukung Industri 4.0 menjadikan pengumpulan, pengolahan, dan penampilan informasi suatu produksi menjadi hal utama. Informasi yang berkaitan dengan produksi dalam hal ini adalah data tentang produk, lokasi produk, dan status dari produk tersebut di dalam satu proses produksi. Proses produksi dimulai dari keberadaan bahan baku di tempat penyimpanan. Daftar barang yang tersedia di tempat penyimpanan ini disebut sebagai inventory. Oleh karena itu, sistem pemantauan harus dimulai dari inventory. Teknologi sensor RFID (Radio Frequency Identifier) dapat membantu untuk mengenali suatu barang dengan mudah, efektif dan efisien. RFID tag yang dipasangkan pada suatu barang akan memberikan informasi tentang detail barang tersebut. Penelitian ini akan berfokus pada analisis kinerja pasif.